The added value of SPECT/spiral CT in patients with equivocal bony metastasis from hepatocellular carcinoma - Zhang, Y.; Shi, H.; Li, B.; Cai, L.; Gu, Y.; Xiu, Y. (Nuklearmedizin - NuclearMedicine, 2015)
The aim of this study was to evaluate the incremental value provided by single-photon emission computed tomography (SPECT)/spiral computed tomography (CT) over SPECT alone for the evaluation of equivocal bone lesions in patients with hepatocellular carcinoma (HCC). Patients, methods: This was a retrospective study of 65 patients (61 men and 4 women; mean age, 53.1 ± 10.1 years; age range, 31–78 years) with HCC confirmed by pathology who underwent planar whole body scintigraphy and SPECT/CT. Each lesion was scored visually using a 5-point scale (0, negative; 1, benign; 2, likely benign; 3, likely bone metastasis; 4, bone metastasis). Lesions in which diagnostic confidence was scored as 3 or 4 were categorized into metastases.The final diagnosis of each lesion was based on pathological confirmation or follow-up by whole body scintigraphy and SPECT/spiral CT conducted two or more times. The diagnostic accuracy, sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of SPECT alone and SPECT/CT were computed. Results: The diagnostic accuracy, sensitivity, specificity, PPV, and NPV of SPECT alone were 78.4, 70.9%, 94.9%, 96.8% and 59.7%, respectively. Moreover, for agreement of SPECT alone and the final results, the kappa value was 0.567 (p < 0.001), which was considered to be moderate agreement. The diagnostic accuracy, sensitivity, specificity, PPV, and NPV of SPECT/CT were 99.2%, 100%, 97.4%, 98.9% and 100 %, respectively. Furthermore, for agreement of SPECT/CT and the final results, the kappa value was 0.981 (p < 0.001), which was considered to be nearly perfect agreement. Conclusions: SPECT/spiral CT is more accurate and valuable than SPECT alone in the differential diagnosis of equivocal bone lesions in patients with HCC.
Keywords: Single photon emission computed tomography / computed tomography; hepatocellular carcinoma; bone; neoplasm metastasis